2009
DOI: 10.1111/j.1447-0756.2009.01120.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of fetal growth restriction complicated later by preeclampsia

Abstract: Preeclampsia with FGR is severe condition which can possibly adversely affect the maternal condition. About 15% of all mothers diagnosed with FGR developed preeclampsia afterwards; therefore, those with FGR are considered to be candidates for close monitoring for the clinical manifestation of preeclampsia, and those with early-onset FGR with proteinuria may represent a high-risk group for preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 22 publications
3
37
0
Order By: Relevance
“…This premise is further strengthened by the significant overlap in their clinical presentations, with evidence suggesting that 12.8–58.6% of women with severe early onset pre-eclampsia will be further complicated by the presence of fetal growth restriction [10], [11]. Conversely, it has been shown that approximately 15% of women diagnosed with FGR will be diagnosed with superimposed pre-eclampsia later in the pregnancy [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This premise is further strengthened by the significant overlap in their clinical presentations, with evidence suggesting that 12.8–58.6% of women with severe early onset pre-eclampsia will be further complicated by the presence of fetal growth restriction [10], [11]. Conversely, it has been shown that approximately 15% of women diagnosed with FGR will be diagnosed with superimposed pre-eclampsia later in the pregnancy [12].…”
Section: Introductionmentioning
confidence: 99%
“…Of clinical interest, several studies have proposed that the combination of pre-eclampsia with FGR is associated with a more severe pre-eclamptic phenotype when compared to women with pre-eclampsia and no FGR [12], [13]. Mitani et al [12] examined 133 women between 22 weeks' gestation and term with pre-eclampsia with or without FGR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…62 In pregnancies in which intrauterine growth restriction due to uteroplacental vascular insufficiency is diagnosed, maternal surveillance for the development of severe preeclampsia with adverse features is warranted. 63,64 Evaluation of placental function by umbilical artery doppler is a clinical standard to distinguish between SGA and FGR. 65,66 …”
Section: Screening and Diagnosismentioning
confidence: 99%
“…Preterm newborns of women who have PE are of great concern because strong evidence shows that they are exposed to increased oxidative stress, which has been implicated in the pathogenesis of serious diseases in neonates [ 53 ]. Thus, an unfavorable outcome could be expected in infants of women who have PE [ 54 ]. Several studies indicate that PE is associated with a higher incidence of newborns with low birth weight [ 55 , 56 ].…”
Section: Low Birth Weight Neonates Born To Preeclamptic/ Eclamptic Momentioning
confidence: 99%